DICOMAddress: modelo distribuído de endereçamento de imagens para uma infraestrutura de informação telerradiológica - Damasceno, Herson Heracles Barreto e (2018)
DAMASCENO, Herson Heracles Barreto. DICOMAddress: Modelo distribuído de endereçamento de imagens para uma infraestrutura de informação telerradiológica. 2018. Dissertação (Mestrado em Informática) – Programa de Pós-Graduação em Informática, Universidade Federal da Paraíba, João Pessoa, 2018. It is known that the use of teleradiology is increasingly present in hospitals and clinics and that studies are located between them via URLs.It is important to note that these studies need to be available for several years (decades) and such URLs must allow access to them in the future, even if the actual location of the studies has been changed. This work proposes a model for addressing studies (exams) of medical images for a teleradiological information infrastructure. It uses the Named Data Networking (NDN) protocol, whose basic premise is the naming of objects for their discovery and retrieval, that is, the addressing is no longer based on location and is now supported in the name given to each object. The objective of this work is to propose the DICOMAddress, a layer that makes the link between the DICOMFlow and the NDN implementation, the NDN Forwarder Daemon, for locating moved objects without modifying the workflow. It is intended to be incorporated into the DICOMFlow distribution protocol for medical studies, which is asynchronous, distributed and uses URLs to locate studies. This template is not intended to change the way images are transferred, but rather aims to name these exams so that it can generate a valid URL to transfer these images. For the validation of the model, a prototype was created where experiments were carried out in a simulated environment in order to validate the proposed model. It was concluded that the proposed model meets the needs of DICOMFlow and was successful in returning the URL with the location of the requested images.